PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF UNTUK MEMFASILITASI BELAJAR MANDIRI MAHASISWA CALON GURU SD PADA KONSEP BILANGAN - Gustimal Witri; Syahrilfuddin Syahrilfuddin; Guslinda Guslinda (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2018)
Interactive Learning Media (ILM) has been developed to represent base of number concept turn into more interactive andmeaningful learning. The first design of ILM is multimedia supported computer that explore number concept in existingconceptual. Pre-service elementary teachers should be provided with the learning that can optimize the number conceptions. Tocollect and analyse data comprehensively, researchers developed a 4D developing method which has comprehensive stages:define, design, develop, and desseminate. The 4D developing stage has been utilized to describe ILM comprehensively. Based ondata analysis, it can be concluded that ILM could effectively improve pre-service teachers‟ conceptual understanding and couldfacilitate self-study of pre-service elementary teachers about number concept.